Essentials of human resource management - Tyson, S. (Shaun); Tyson, S. (Shaun). (Amsterdam ; London : Butterworth-Heinemann, 2006)
Designed for all managers or potential managers seeking to acquire knowledge, skills and techniques for the management of people at work, this text combines a commentary on organisational behaviour with an explanation of HRM techniques.
Title from e-book title screen (viewed October 15, 2007).
Includes bibliographical references and index.
Also available in print.
Keywords: Personnel management